Improvement in activities and participation in an adolescent following secondary foot amputation - Marion Prigent; Sylvain Brochard; Matthias Thepaut; Thierry Cornic; M.T. Cariou; Catherine Le Rouzic; Philippe Le Moine; Christelle Pons; Laetitia Houx (Elsevier, 2020)
Background: When severe limb trauma occurs in a child, all efforts are made to preserve the limb as far as possible. In rare cases, however, secondary amputation may be necessary to improve functional outcome and participation. Case report: In this paper, we report on a young adolescent male with a severe loss of function following foot trauma, who underwent secondary trans-tibial amputation 17 months post injury. This paper describes how a structured multidisciplinary approach around the child and his family led to a successful outcome. Clinical rehabilitation impact: It is hoped that this case report may help other health professionals with decision-making in cases of secondary amputations, and to implement appropriate follow-up for such patients.